DEMOCRACY, MINORITY UNIONS AND THE RIGHT TO STRIKE: A CRITICAL ANALYSIS Numsa v Bader Bop (Pty) Ltd 2003 2 BCLR (CC) - MA Chicktay (Obiter, 2022)
In NUMSA v Bader Bop (Pty) Ltd (2003 2 BCLR 182 (CC)) minority unions were given the right to strike for the purpose of acquiring organisational rights. The Constitutional Courts approach in coming to its conclusion is questionable. Instead of declaring sections of the Labour Relations Act 66 of 1995 (hereinafter “the LRA”) unconstitutional it sought to bastardize the language of the Act and maintain its validity. A literal interpretation of the Act clearly prohibited strikes. The Constitutional Court should have declared these sections invalid and referred them to the legislature to correct. This judgment also fails to apply International Labour Organisation (ILO) standards correctly and is a major step backwards in protecting our new constitutional democracy. The purpose of this case note is to show weakness within the approach adopted by the Constitutional Court and suggest the approach that the court should have adopted.